2004
DOI: 10.1097/01.brs.0000109983.12113.9b
|View full text |Cite
|
Sign up to set email alerts
|

Free Hand Pedicle Screw Placement in the Thoracic Spine: Is it Safe?

Abstract: The free hand technique of thoracic pedicle screw placement performed in a step-wise, consistent, and compulsive manner is an accurate, reliable, and safe method of insertion to treat a variety of spinal disorders, including spinal deformity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
523
2
36

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 659 publications
(575 citation statements)
references
References 47 publications
14
523
2
36
Order By: Relevance
“…The use of intra-operative fluoroscopy for placement of pedicle screws has resulted in prolonged fluro time and radiation exposure to the surgical personnel and patient [32]. However, we have found that free-hand technique is relatively easy to learn and is as accurate [22] as the other methods, which were implemented in our study. There are also various intraoperative methods, such as SSEP, MEP or computer assisted surgery [11,29], described to detect pedicle violation or neural injury.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…The use of intra-operative fluoroscopy for placement of pedicle screws has resulted in prolonged fluro time and radiation exposure to the surgical personnel and patient [32]. However, we have found that free-hand technique is relatively easy to learn and is as accurate [22] as the other methods, which were implemented in our study. There are also various intraoperative methods, such as SSEP, MEP or computer assisted surgery [11,29], described to detect pedicle violation or neural injury.…”
Section: Introductionmentioning
confidence: 75%
“…So, accurate and safe placement of screw within the pedicle is a crucial step during the surgery. Various methods such as free hand technique, Penfield outside-in technique, under C-arm control, computer assisted navigational surgery and stereotectic surgery, etc., to put the pedicle screw have been described in the literature [20,22,29]. The use of intra-operative fluoroscopy for placement of pedicle screws has resulted in prolonged fluro time and radiation exposure to the surgical personnel and patient [32].…”
Section: Introductionmentioning
confidence: 99%
“…Most of these studies, however, describe different entry points at different levels as well as different insertion techniques. In our department, we used the method reported by Kim et al [9] to determine thoracic entry point, and the method reported by Magerl [10] to determine the lumbar entry point. This resulted in a high accuracy rate and a low complication rate in placement of screw in patients with moderate scoliosis.…”
Section: Introductionmentioning
confidence: 99%
“…In a report by Suk et al 24 , the perforation rate of pedicle screw inserted by free hand in AIS posterior fusion was 1.5%; however, only 10% of cases were evaluated by CT, and thus this reported rate is not highly reliable. In report by Kim et al 25 In contrast, the perforation rates of reports of surgeries that employed navigation system [28][29][30] were between 1.8 and 11.4%. In the present report, the rate was as low as 2.8%.…”
Section: Discussionmentioning
confidence: 99%